2015
DOI: 10.1016/j.hbrcj.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Study of reinforcement corrosion in expanded clay concrete

Abstract: Expanded clay concrete differs from heavy-weight concrete not only by the composition and performance properties, but also by modes of chemical interactions between the components. So, not the primary problem of reinforcement corrosion in heavy-weight concrete under the normal conditions and the correct protective layer, becomes in the major problem in expanded clay concrete. The issue of reinforcement corrosion in expanded clay concrete is considered in this article. The studies on the effect of different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also in the course of the research it was found that the slag concrete resistance coefficient under the action of sulfate media was 0,92-1,4, and under the action of slightly acidic it was 1,2-1,26, under the rated -0.8. Consequently, the proposed concrete can be used under the mild acidic and sulphate aggression [7][8][9][10][11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…Also in the course of the research it was found that the slag concrete resistance coefficient under the action of sulfate media was 0,92-1,4, and under the action of slightly acidic it was 1,2-1,26, under the rated -0.8. Consequently, the proposed concrete can be used under the mild acidic and sulphate aggression [7][8][9][10][11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…The open and closed pores of ECA, also, contribute to improving the properties of concrete against chloride penetration and reinforcement corrosion. Other authors, i.e., Chidighikaobi (2019), Dabbaghi et al, (2021), Ismail and Halim (2020), and Uglyanitsa et al, (2015), demonstrated that mixtures with ECA have higher thermal insulation and less affected than ordinary concrete after exposure to high temperatures or after cooling, which is favorable to improving the energy consumption of buildings. Several studies (Nahhab and Ketab, 2020;Nepomuceno, 2018;Ismail and Halim, 2020;Muñoz et al, 2018) found that the properties of mortars and concretes containing ECA depend on the size and shape of aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Rashad (2018), Ahmad et al (2019) Bogas et al (2012) Nahhab and Ketab (2020), Bogas et al (2015), and Nepomuceno (2018) indicated that increasing the ECA content affects the sorption coefficient, porosity, and generates separation between aggregates and mortar compared to conventional concrete. The authors of Rashad (2018), Ismail and Halim (2020), Uglyanitsa et al (2015) reported that open and closed pores of ECA have an advantage in the formation of bonds between aggregates and cement paste. The open and closed pores of ECA, also, contribute to improving the properties of concrete against chloride penetration and reinforcement corrosion.…”
Section: Introductionmentioning
confidence: 99%